Family Motivation In The Provision Of Nutrition With Stunting Events In Tons Of Together In Pujiharjo Village, Tirtoyudo District - fazrin, Intan; Luluk Fidyaswati (Journal of Global Research in Public Health, 2021)
ABSTRACT Family motivation can be shown by efforts to prevent stunting. Family motivation is closely related to food security which can be illustrated by changes in food consumption that lead to a decrease in quantity and quality, including changes in the frequency of consumption of staple foods. The researcher aims to analyze the relationship between family motivation in providing nutrition with the incidence of stunting in toddlers in Pujiharjo Village, Tirtoyudo District. The analysis was carried out to analyze the relationship of family motivation in providing nutrition with the incidence of stunting in toddlers in Pujiharjo Village, Tirtoyudo District, using correlation analysis. The results of the analysis that has been carried out on 32 respondents, namely mothers who have toddlers in Pujiharjo Village, Tirtoyudo District, it can be concluded that most of the respondents have family motivation in providing nutrition which is included in the high criteria. The results of the analysis of the incidence of stunting can be seen that most of them have children who are in the normal category. From the results of the analysis, it can also be seen that there is a significant relationship between family motivation in providing nutrition with the incidence of stunting in toddlers in Pujiharjo Village, Tirtoyudo District. This means that with increasing family motivation in providing nutrition, the incidence of stunting in toddlers in Pujiharjo Village, Tirtoyudo District will decrease.